2010
DOI: 10.1105/tpc.108.064816
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsis thalianaSTYLISH1 Protein Acts as a Transcriptional Activator Regulating Auxin Biosynthesis  

Abstract: The establishment and maintenance of auxin maxima in vascular plants is regulated by auxin biosynthesis and polar intercellular auxin flow. The disruption of normal auxin biosynthesis in mouse-ear cress (Arabidopsis thaliana) leads to severe abnormalities, suggesting that spatiotemporal regulation of auxin biosynthesis is fundamental for normal growth and development. We have shown previously that the induction of the SHORT-INTERNODES/STYLISH (SHI/STY) family member STY1 results in increased transcript levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 56 publications
7
161
1
8
Order By: Relevance
“…These were dominated by genes involved in auxin signaling and brassinosteroid biosynthesis. In addition, two of the putative EBB1 gene targets encode SHORT INTERNODE RELATED SEQUEN-CES (SRS), which are transcription factors that have been implicated in regulation of auxin biosynthesis in Arabidopsis through activation of the YUCCA gene (41,42). In support of our findings, recent evidence suggests that auxin is important for reinitiating growth after dormancy (43).…”
Section: Discussionsupporting
confidence: 76%
“…These were dominated by genes involved in auxin signaling and brassinosteroid biosynthesis. In addition, two of the putative EBB1 gene targets encode SHORT INTERNODE RELATED SEQUEN-CES (SRS), which are transcription factors that have been implicated in regulation of auxin biosynthesis in Arabidopsis through activation of the YUCCA gene (41,42). In support of our findings, recent evidence suggests that auxin is important for reinitiating growth after dormancy (43).…”
Section: Discussionsupporting
confidence: 76%
“…We recently showed that SHORT INTERNODES/ STYLISH (SHI/STY) family members are important throughout plant development and directly regulate YUC4-mediated auxin biosynthesis in Arabidopsis Ståldal et al, 2008;Eklund et al, 2010a), and we could show that transcription of YUC8 was activated by STY1 (Eklund et al, 2010a). This suggests that the temporal and spatial regulation of SHI/STY family members may be crucial for the developmental regulation of auxin production.…”
mentioning
confidence: 56%
“…The carpel valve length is significantly reduced in plants with a reduced level of SHI/STY gene activity, such as the SHI/STY quintuple mutant, and in plants expressing a STY1 protein transformed from a transcriptional activator to a repressor by the addition of a C-terminal SRDX tag Eklund et al, 2010a). Interestingly, it was recently demonstrated that around 25% of the drn-1 drnl-1 flowers have one or two shortened carpel valves and/or are missing one valve (Chandler et al, 2011b; Table II).…”
Section: Loss Of Drn Drnl and Puchi Functions Results In Reduced Stmentioning
confidence: 99%
“…S4). Utilization of chimeric repressors is an established and effective approach to investigating the loss of function phenotypes of transcription activators when they have a degree of functional redundancy with other related proteins [37][38][39][40][41] . Transgenic Arabidopsis lines expressing NLP6-SUPRD were generated by transformation of the 4 Â NRE-min-GUS line 28 (WT in Fig.…”
Section: Resultsmentioning
confidence: 99%